Point of equilibrity. A narrative video game on decision-making during the COVID-19 pandemic crisis - Chrysanthi, Angeliki; Katifori, Akrivi; Kapralos, Alexandros; Magklis, Aristotelis; Antoniou, Angeliki (Frontiers in Computer Science, 2023)
Point of Equilibrity (PoE) is a narrative game designed and developed with the aim to simulate the the covid-19 pandemic from a government’s point of view and offer different perspectives on the complexity of managing a pandemic crisis. The players are called to make important decisions during a health crisis in the simulated environment while considering significant historic and topical events, as well as possible economic, political, and social implications. This paper presents the results of a user study with 37 adult participants aiming to examine (1) the effect of PoE gameplay on the players’ perspective on the management of the covid-19 pandemic crisis, and (2) the effect of the players’ FFM and DMQ personality traits profile on the game experience and the decision-making process. The participants played the game and then were asked to fill in an on-line questionnaire. The results suggest that the game design offered an engaging game experience and was effective to promote reflection and perspective taking on different aspects of crisis management, as well as the supporting role of relevant historical information in the decision-making process. The study also reports correlations between specific personality traits, such the DMQ Thoroughness and Principled, the FFM Conscientiousness and Openness to experience with specific aspects of the game experience, such as absorption, perspective taking and the preference for more choices in the gameplay.